A Novel Legumain-Like Protease in Macrobrachium nipponense: Identification, Characterization, and Function Analysis in Ovary Maturation - Jiang, Sufei; Xiong, Yiwei; Zhang, Wenyi; Zhu, Junpeng; Cheng, Dan; Gong, Yongsheng; Wu, Yan; Qiao, Hui; Fu, Hongtuo (Frontiers in Endocrinology, 2022)
Legumain, also called aspartic endopeptidase (AEP), was a member of the cysteine proteases family and involved in various physiological processes. In this study, we analyzed the characteristics a novel legumain-like (named Mn-Lel) in the female oriental river prawn, Macrobrachium nipponense which was involved in ovary maturation. The Mn-Lel was1454 bp in length, including a 1290 bp open reading frame that encoded 430 amino acids. qPCR analysis indicated that Mn-Lel was specific highly expressed in the hepatopancreas and ovaries of female prawns. It was rarely expressed in embryogenesis and weakly expressed in early larval development stages and then expressed significantly increased after metamorphosis, which indicated that Mn-Lel was not a maternal gene and mainly plays a role in adults. During the different ovarian stages, Mn-Lel expression in the hepatopancreas had no obvious rules, while its expression in the ovaries had a significant peak in stage Ⅲ. In situ hybridization studies revealed that Mn-Lel was localized in the oocyte of the ovary. Changes in the gonad somatic index confirmed the inhibitory effects of Mn-Lel dsRNA on ovary maturation. These results suggest that Mn-Lel has a key role in promoting ovary maturation.